High performance polypropylene cable jacket and method of making same
Patent Information
- Application Number
- CN202611138352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
上述现有技术方案体系中大量填充滑石粉、轻质碳酸钙等无机填料,其与聚丙烯基体的界面相容性较差,在摩擦受力过程中易发生填料脱落并作为硬质磨粒加速表面磨损进程;另一方面,为改善韧性引入的大量乙丙橡胶相,会降低材料整体的表面硬度与抗划伤能力,最终导致聚丙烯电缆护套在复杂工况下易出现表面磨耗超标、护套层变薄甚至磨穿破损的问题,存在耐磨性能不佳的缺陷,严重制约了聚丙烯护套材料在高磨损敷设场景下的推广应用
1、本申请采用聚四氟乙烯原位负载硅灰石晶须作为核心耐磨功能组分,有效解决了现有体系中无机填料易脱落形成二次磨粒、固体润滑剂易迁移析出的技术缺陷。该组分以一维硅灰石晶须为刚性承载基底,可在聚丙烯基体中搭建三维增强骨架,显著提升材料的表面硬度与抗压缩形变能力,抵消增韧组分引入带来的硬度衰减,减小摩擦过程中的犁沟切削深度与材料剥落量,阻碍磨痕横向扩展。同时,原位锚定在晶须表面的聚四氟乙烯润滑组分,可随摩擦服役过程中的微量磨损匀速释放,在接触界面形成连续稳定的低摩擦转移膜,将硬质滑动摩擦转化为低阻力剪切作用;且锚定型结构避免了游离润滑剂易团聚、过早迁移析出的问题,润滑作用更长效,实现了刚性增强与减摩润滑的一体化协同增效。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, and more specifically, to a high-performance polypropylene cable sheath and its preparation method. Background Technology
[0002] Power cables and communication cables are the core foundation of power transmission and signal transmission systems, widely used in urban power grids, rail transit, new energy projects, industrial and mining enterprises, and civil buildings. The cable sheath, as the outermost protective structure of the cable, plays a crucial role in insulation, mechanical buffering, waterproofing, moisture protection, weather resistance, corrosion resistance, and resistance to external damage. Its material properties directly determine the cable's suitability for installation, operational stability, and long-term service life. Compared to traditional polyvinyl chloride (PVC) and ordinary polyethylene (PE) sheath materials, polypropylene (PP) materials possess numerous advantages such as high heat resistance, good insulation, chemical corrosion resistance, recyclability, and excellent processability. It is gradually becoming the mainstream base material for mid-to-high-end cable sheaths, effectively compensating for the shortcomings of traditional sheaths, such as insufficient heat resistance, easy aging, and lack of environmental friendliness.
[0003] In related technologies, such as patent application CN112126156A, a radiation-resistant polypropylene cable sheath material is disclosed. Its characteristic is that it is made from the following raw materials in parts by weight: 10-50 parts polypropylene, 20-40 parts talc, 15-25 parts CCR603 light calcium carbonate, 5-10 parts DOTP plasticizer, 5-10 parts US70 resin powder, 1-10 parts PL500 crosslinking agent, 1-3 parts polyethylene wax, 1-3 parts semi-refined paraffin wax, 1-3 parts antioxidant, 1-3 parts YL-18A flame retardant, 1-3 parts magnesium oxide, 10-15 parts carbon black, 1-10 parts TJ1016-A2 stabilizer, 1-30 parts COPT-40 ethylene propylene rubber, and 5-20 parts 4045 ethylene propylene rubber. The weight ratio of polypropylene, COPT-40 ethylene propylene rubber, and 4045 ethylene propylene rubber is 2:1.2:1. The above technical solution improves the flexibility of the polypropylene system by introducing EPDM rubber into it, allowing the energy absorbed by the cable sheath material under irradiation to be transferred to the EPDM rubber segments for release. At the same time, by adjusting the ratio between polypropylene and different functional EPDM rubber components, the thermal life and radiation resistance of the cable sheath material are effectively improved.
[0004] However, in actual cable laying, installation, and long-term service, the cable sheath must continuously withstand the scraping friction during laying and dragging, the abrasive wear of sand and soil, and the reciprocating friction caused by operating vibration. The existing technical solutions mentioned above use a large amount of inorganic fillers such as talc and light calcium carbonate, which have poor interfacial compatibility with the polypropylene matrix. During frictional stress, these fillers are prone to detachment and act as hard abrasive particles, accelerating surface wear. On the other hand, the large amount of ethylene propylene rubber phase introduced to improve toughness reduces the overall surface hardness and scratch resistance of the material. Ultimately, this leads to excessive surface wear, thinning of the sheath layer, and even wear-through damage in polypropylene cable sheaths under complex working conditions, resulting in poor wear resistance and severely restricting the widespread application of polypropylene sheath materials in high-wear laying scenarios. Summary of the Invention
[0005] To improve the wear resistance of polypropylene cable sheaths, this application provides a high-performance polypropylene cable sheath and its preparation method.
[0006] This application provides a high-performance polypropylene cable sheath, which adopts the following technical solution: A high-performance polypropylene cable sheath comprises the following raw materials in parts by weight: 60-80 parts of polypropylene; 8-18 parts of ethylene-octene copolymer; 6-15 parts of polytetrafluoroethylene in situ supported on wollastonite whiskers; 3-10 parts of modified hexagonal boron nitride nanosheets; 10-20 parts aluminum hydroxide; 1-3 parts carbon black; 2-5 parts compatibilizer; Antioxidant 0.3-1.2 parts; Light stabilizer 0.2-0.8 parts; 0.5-1.5 parts of auxiliary agent; The polytetrafluoroethylene in-situ supported wollastonite whiskers are obtained by in-situ deposition of nano-polytetrafluoroethylene particles on the surface of wollastonite whiskers as a substrate. The modified hexagonal boron nitride nanosheets are prepared by hydroxylating and etching hexagonal boron nitride nanosheets and then grafting silane coupling agents onto them.
[0007] By employing the above technical solutions, the surface hardness and resistance to compressive deformation of the material are jointly improved through the three-dimensional framework bearing effect of wollastonite whiskers and the layered reinforcement effect of hexagonal boron nitride nanosheets. This effectively offsets the hardness reduction caused by the introduction of ethylene-octene copolymer, breaking the performance contradiction that "toughening inevitably reduces wear resistance." The rigid filler network can significantly reduce the depth of furrows and the amount of material shedding during friction, hindering the lateral expansion of wear tracks and improving the sheath's resistance to abrasive wear and scratches.
[0008] In terms of friction reduction and lubrication, this solution employs in-situ loading to anchor polytetrafluoroethylene (PTFE) nanoparticles onto the surface of wollastonite whiskers. This, combined with the layered crystal lubrication properties of hexagonal boron nitride (BON), forms a dual synergistic lubrication mechanism. During frictional service, the anchored PTFE component is gradually released with the minute wear of the whiskers, forming a continuous and stable low-friction coefficient transfer film at the friction interface. This transforms hard sliding friction into low-resistance shear between lubricating film layers. Simultaneously, the interlayer slip effect of BON further reduces interfacial frictional resistance and minimizes adhesive wear. Compared to free-state added solid lubricants, the anchored lubricating component is less prone to migration and precipitation, resulting in a longer-lasting lubricating effect.
[0009] The overall system enhances abrasion resistance while also considering the flame retardancy, insulation, weather resistance, and processability required for cable sheathing. The aluminum hydroxide component imparts halogen-free flame retardant properties to the material, and after interface optimization, it does not negatively impact abrasion resistance. Carbon black, along with the photo-oxidation and antioxidant systems, synergistically improves the material's weather aging resistance, ensuring the stability of abrasion resistance during long-term service. The ethylene-octene copolymer maintains the low-temperature toughness and impact resistance of the sheath material, meeting the mechanical requirements of cable laying and service. This system achieves a balance between abrasion resistance and other core properties, making it suitable for high-wear laying scenarios.
[0010] Optionally, the polytetrafluoroethylene-supported wollastonite whiskers are prepared by the following method: A1. Add wollastonite whiskers to an aqueous sodium hydroxide solution, heat to 70-90℃, stir for 2-4 hours, filter and wash, and dry at 100-110℃ for 6-8 hours to obtain hydroxylated wollastonite whiskers. A2. Add hydroxylated wollastonite whiskers to deionized water and ultrasonically disperse for 15-30 min. Then add polytetrafluoroethylene dispersion emulsion, adjust the pH of the system to 3-4, heat to 65-75℃, and stir for 3-5 h. Then filter the suspension, wash the filter cake with deionized water 3-5 times, dry at 100-120℃ for 4-6 h, and then place it in a muffle furnace and sinter at 360-380℃ under a nitrogen atmosphere for 1-2 h. After cooling, pulverize to obtain polytetrafluoroethylene-supported wollastonite whiskers.
[0011] By employing the above-mentioned technical solution, a robust polytetrafluoroethylene (PTFE) lubricating layer can be constructed on the surface of wollastonite whiskers through a process involving alkaline etching, hydroxylation, and in-situ deposition and sintering. The alkaline etching process introduces abundant active hydroxyl groups onto the whisker surface, providing sufficient reaction sites for the anchoring of PTFE particles. Subsequent high-temperature sintering allows the PTFE particles to melt and bond, forming a stable interface with the whisker surface. This prevents premature detachment of the lubricating layer during friction, ensuring a long-lasting friction-reducing effect while maximizing the preservation of the one-dimensional structural integrity and mechanical reinforcement of the wollastonite whiskers.
[0012] Optionally, in step A1, the mass concentration of the sodium hydroxide aqueous solution is 5%-10%; the mass ratio of the wollastonite whiskers to the sodium hydroxide aqueous solution is 1:(8-12).
[0013] By adopting the above technical solution, this parameter range can achieve a balance between the degree of surface activation and structural integrity of the whiskers. A moderate alkaline etching intensity can introduce sufficient active hydroxyl groups onto the wollastonite surface to ensure subsequent load-bearing performance, while avoiding damage to the whisker's aspect ratio and mechanical strength due to excessive etching, thus preventing a decrease in the whisker's own reinforcing load-bearing capacity and ensuring its stable performance as a skeletal support in the wear-resistant system.
[0014] Optionally, in step A2, the mass ratio of the hydroxylated wollastonite whiskers, deionized water, and polytetrafluoroethylene dispersion emulsion is 1:(9-12):(0.3-0.8); and the solid content of the polytetrafluoroethylene dispersion emulsion is 20%-30%.
[0015] Optionally, the modified hexagonal boron nitride nanosheets are prepared using the following method: B1. Add hexagonal boron nitride nanosheets to a mixed acid solution, ultrasonically disperse for 20-40 min, heat to 85-95℃, reflux etching for 5-7 h, and obtain hydroxylated hexagonal boron nitride nanosheets after filtration, washing and drying. B2. Add hydroxylated hexagonal boron nitride nanosheets to an ethanol solution and ultrasonically disperse for 20-30 min. Then add silane coupling agent KH-550, adjust the pH of the system to 4-5 with glacial acetic acid, heat to 60-70℃, and stir for 4-6 h. After the reaction is complete, centrifuge, wash with ethanol 3-5 times, and vacuum dry at 80-100℃ for 5-7 h to obtain modified hexagonal boron nitride nanosheets.
[0016] By employing the above technical solution, a two-step process of mixed acid hydroxylation etching and silane coupling agent grafting can significantly improve the interfacial compatibility between hexagonal boron nitride and the polypropylene matrix. Mixed acid etching introduces active functional groups at the edges and defects of the lamellar structure, providing reaction sites for the covalent grafting of the silane coupling agent. The grafted organic molecular chains can form good molecular entanglement with the polyolefin matrix, preventing the stacking and aggregation of two-dimensional lamellars, and simultaneously preventing the lamellars from peeling off from the matrix during friction to form abrasive particles, thus ensuring the stable performance of its toughening, strengthening, and lubricating effects.
[0017] Optionally, in step B1, the mixed acid solution is concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (3-4):1; the mass ratio of the hexagonal boron nitride nanosheets to the mixed acid solution is 1:(20-30).
[0018] Optionally, in step B2, the mass concentration of the ethanol solution is 80%-90%, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the ethanol solution is 1:(10-15), and the amount of silane coupling agent KH-550 added is 1%-4% of the mass of the hydroxylated hexagonal boron nitride nanosheets.
[0019] By employing the above technical solution, under these reaction conditions, the silane coupling agent can be fully hydrolyzed and undergo a dehydration condensation reaction with the hydroxyl groups on the boron nitride surface to form a uniform organic grafted layer. A moderate amount of coupling agent ensures sufficient surface grafting, effectively improving interfacial compatibility, while also preventing excessive self-polymerization due to excessive coupling agent. This guarantees the dispersion effect and interfacial bonding strength of the modified filler in the matrix, thereby steadily improving the wear resistance of the material.
[0020] Optionally, the molecular weight of the polypropylene is 250,000 to 450,000.
[0021] Optionally, the additive is a mixture of polyethylene wax and calcium stearate in a mass ratio of (2-3):1; the compatibilizer is maleic anhydride-grafted polypropylene.
[0022] This application also provides a method for preparing a high-performance polypropylene cable sheath, using the following technical solution: A method for preparing a high-performance polypropylene cable sheath includes the following steps: S1. Polypropylene, ethylene-octene copolymer, polytetrafluoroethylene in-situ supported wollastonite whiskers, modified hexagonal boron nitride nanosheets, aluminum hydroxide, carbon black, compatibilizer, antioxidant, light stabilizer and additives are put into a high-speed mixer and mixed at 70-85℃ and 900-1200r / min for 6-12min to obtain a premix. S2. The premixed material is added to a twin-screw extruder, melt-blended, extruded, water-cooled, and pelletized to obtain cable sheath granules. The cable sheath granules are added to a single-screw extruder, melt-plasticized, and extruded to coat the surface of the cable core. Then, the material is shaped, drawn, and wound in a cooling water tank to obtain a high-performance polypropylene cable sheath.
[0023] A stepwise process involving high-speed premixing, twin-screw blending and granulation, and single-screw extrusion coating ensures uniform dispersion of all functional components within the matrix. Appropriate mixing temperature and speed prevent filler agglomeration, ensuring uniform distribution of reinforcing and lubricating components throughout the material. Suitable extrusion temperature and screw speed guarantee full plasticization of the matrix without thermal degradation, resulting in a dense and uniform internal structure of the sheath material. Macroscopically, this manifests as stable and reliable wear resistance, good batch-to-batch consistency, and meets the requirements of industrial production and actual service.
[0024] In summary, this application has the following beneficial effects: 1. This application uses polytetrafluoroethylene (PTFE) in-situ supported wollastonite whiskers as the core wear-resistant functional component, effectively solving the technical defects of existing systems, such as the easy detachment of inorganic fillers forming secondary abrasive particles and the easy migration and precipitation of solid lubricants. This component uses one-dimensional wollastonite whiskers as a rigid load-bearing substrate, which can build a three-dimensional reinforcing skeleton in a polypropylene matrix, significantly improving the surface hardness and compressive deformation resistance of the material, offsetting the hardness reduction caused by the introduction of toughening components, reducing the ploughing depth and material spalling during friction, and hindering the lateral expansion of wear tracks. Simultaneously, the PTFE lubricating component in-situ anchored on the whisker surface can be released uniformly with the minute wear during friction service, forming a continuous and stable low-friction transfer film at the contact interface, transforming hard sliding friction into low-resistance shearing action; and the anchored structure avoids the problems of free lubricant agglomeration and premature migration and precipitation, resulting in longer-lasting lubrication and achieving integrated synergistic effects of rigidity enhancement and friction reduction lubrication.
[0025] 2. This application employs modified hexagonal boron nitride nanosheets as another core functional component, forming a one-dimensional-two-dimensional hybrid reinforcement system with wollastonite whiskers, thus resolving the performance contradiction of not being able to simultaneously achieve toughening and wear resistance in existing technologies. After hydroxylation etching and silane coupling agent grafting modification, the interfacial compatibility between the hexagonal boron nitride nanosheets and the polypropylene matrix is significantly improved, allowing them to be uniformly dispersed in the matrix and avoiding problems such as layer stacking, agglomeration, and frictional peeling. The two-dimensional layered structure can form a scale-gradient filling with the one-dimensional whiskers, synergistically strengthening the surface hardness and scratch resistance of the material, further offsetting the hardness reduction caused by the ethylene-octene copolymer; at the same time, hexagonal boron nitride itself has a typical layered crystal structure, which easily undergoes interlayer slippage during friction, playing an auxiliary solid lubrication role, reducing interfacial frictional resistance, reducing adhesive wear, and forming a dual lubrication synergy with the polytetrafluoroethylene on the whisker surface, comprehensively improving the wear resistance of the sheath material. Detailed Implementation
[0026] The present application will be further described in detail below with reference to the embodiments.
[0027] Example of in-situ supported wollastonite whiskers on polytetrafluoroethylene Preparation Example 1 In-situ supported wollastonite whiskers on polytetrafluoroethylene were prepared using the following method: A1. Weigh 100g of wollastonite whiskers and add them to 800g of 5% sodium hydroxide aqueous solution. Stir well and heat to 70℃. Keep warm and stir for 2h to perform surface etching and activation. After the reaction is complete, filter while hot. Wash the filter cake repeatedly with deionized water until the filtrate is neutral. Place the filter cake in a forced-air drying oven and dry at 100℃ for 6h to obtain hydroxylated wollastonite whiskers.
[0028] A2. Weigh 100g of the above-mentioned hydroxylated wollastonite whiskers, add them to 900g of deionized water, and ultrasonically disperse for 15min to form a uniform suspension; add 30g of polytetrafluoroethylene dispersion emulsion with a solid content of 20%, stir evenly, adjust the pH of the system to 3 with 0.1mol / L dilute hydrochloric acid, heat to 65℃, and keep stirring for 3h to allow the nano-polytetrafluoroethylene particles to be deposited in situ on the surface of the wollastonite whiskers; after the reaction is complete, filter the suspension, wash the filter cake three times with deionized water, and dry it at 100℃ for 4h; then place the dried material in a muffle furnace, purge with nitrogen for protection, sinter at 360℃ for 1h, and after natural cooling, remove and pulverize to obtain polytetrafluoroethylene-supported wollastonite whiskers.
[0029] Preparation Example 2 In-situ supported wollastonite whiskers on polytetrafluoroethylene were prepared using the following method: A1. Weigh 100g of wollastonite whiskers and add them to 1000g of 7.5% sodium hydroxide aqueous solution. Stir well and heat to 80℃. Keep warm and stir for 3h to perform surface etching and activation. After the reaction is complete, filter while hot. Wash the filter cake repeatedly with deionized water until the filtrate is neutral. Place the filter cake in a forced-air drying oven and dry at 105℃ for 7h to obtain hydroxylated wollastonite whiskers.
[0030] A2. Weigh 100g of the above-mentioned hydroxylated wollastonite whiskers, add them to 1050g of deionized water, and ultrasonically disperse for 20min to form a uniform suspension; add 55g of polytetrafluoroethylene dispersion emulsion with a solid content of 25%, stir evenly, adjust the pH of the system to 3.5 with 0.1mol / L dilute hydrochloric acid, heat to 70℃, and keep stirring for 4h to allow the nano-polytetrafluoroethylene particles to be deposited in situ on the surface of the wollastonite whiskers; after the reaction is complete, filter the suspension, wash the filter cake 4 times with deionized water, and dry it at 110℃ for 5h; then place the dried material in a muffle furnace, purge with nitrogen, sinter at 370℃ for 1.5h, cool naturally, and then crush to obtain polytetrafluoroethylene-supported wollastonite whiskers.
[0031] Preparation Example 3 In-situ supported wollastonite whiskers on polytetrafluoroethylene were prepared using the following method: A1. Weigh 100g of wollastonite whiskers and add them to 1200g of 10% sodium hydroxide aqueous solution. After stirring evenly, heat the solution to 90℃ and keep it at that temperature for 4 hours to perform surface etching and activation. After the reaction is complete, filter the solution while it is hot. Wash the filter cake repeatedly with deionized water until the filtrate is neutral. Place the filter cake in a forced-air drying oven and dry it at 110℃ for 8 hours to obtain hydroxylated wollastonite whiskers.
[0032] A2. Weigh 100g of the above-mentioned hydroxylated wollastonite whiskers and add them to 1200g of deionized water. Disperse the mixture ultrasonically for 30min to form a uniform suspension. Add 80g of polytetrafluoroethylene dispersion emulsion with a solid content of 30%, stir evenly, and adjust the pH of the system to 4 with 0.1mol / L dilute hydrochloric acid. Heat the mixture to 75℃ and keep it at that temperature for 5h, so that the nano-polytetrafluoroethylene particles are deposited in situ on the surface of the wollastonite whiskers. After the reaction is complete, filter the suspension, wash the filter cake 5 times with deionized water, and dry it at 120℃ for 6h. Then place the dried material in a muffle furnace, purge it with nitrogen for protection, sinter it at 380℃ for 2h, and after natural cooling, take it out and crush it to obtain polytetrafluoroethylene-supported wollastonite whiskers.
[0033] Preparation example of modified hexagonal boron nitride nanosheets Preparation Example 4 Modified hexagonal boron nitride nanosheets were prepared using the following method: B1. Weigh 50g of hexagonal boron nitride nanosheets and add them to 1000g of a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1. Disperse the mixture by ultrasonication for 20min to ensure uniform dispersion of the powder. Heat the system to 85℃ and reflux for etching for 5h to perform hydroxylation modification. After the reaction is complete, slowly pour the reaction solution into 5 times its volume of deionized water to dilute it. After standing, filter the solution. Wash the filter cake repeatedly with deionized water until the supernatant is neutral. Dry the supernatant under vacuum at 80℃ for 5h to obtain hydroxylated hexagonal boron nitride nanosheets.
[0034] B2. Weigh 50g of the above-mentioned hydroxylated hexagonal boron nitride nanosheets and add them to 500g of 80% ethanol aqueous solution. Disperse the solution by ultrasonication for 20min to form a uniform dispersion. Add 0.5g of silane coupling agent KH-550, adjust the pH of the system to 4 with glacial acetic acid, heat to 60℃, and stir for 4h to carry out grafting modification. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate three times with anhydrous ethanol and dry it under vacuum at 80℃ for 5h to obtain modified hexagonal boron nitride nanosheets.
[0035] Preparation Example 5 Modified hexagonal boron nitride nanosheets were prepared using the following method: B1. Weigh 50g of hexagonal boron nitride nanosheets and add them to 1250g of a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3.5:1. Disperse the mixture by ultrasonication for 30min to ensure uniform dispersion of the powder. Heat the system to 90℃ and reflux for etching for 6h to perform hydroxylation modification. After the reaction is complete, slowly pour the reaction solution into 5 times its volume of deionized water to dilute it. After standing, filter the solution. Wash the filter cake repeatedly with deionized water until the supernatant is neutral. Dry the supernatant under vacuum at 90℃ for 6h to obtain hydroxylated hexagonal boron nitride nanosheets.
[0036] B2. Weigh 50g of the above-mentioned hydroxylated hexagonal boron nitride nanosheets and add them to 625g of 85% ethanol aqueous solution. Disperse the solution by ultrasonication for 25min to form a uniform dispersion. Add 1.25g of silane coupling agent KH-550, adjust the pH of the system to 4.5 with glacial acetic acid, heat to 65℃, and stir for 5h to carry out grafting modification. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate 4 times with anhydrous ethanol and dry it under vacuum at 90℃ for 6h to obtain modified hexagonal boron nitride nanosheets.
[0037] Preparation Example 6 Modified hexagonal boron nitride nanosheets were prepared using the following method: B1. Weigh 50g of hexagonal boron nitride nanosheets and add them to 1500g of a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 4:1. Disperse the mixture by ultrasonication for 40min to ensure uniform dispersion of the powder. Heat the system to 95℃ and reflux for etching for 7h to perform hydroxylation modification. After the reaction is complete, slowly pour the reaction solution into 5 times the volume of deionized water to dilute it. After standing, filter the solution. Wash the filter cake repeatedly with deionized water until the supernatant is neutral. Dry the supernatant under vacuum at 100℃ for 7h to obtain hydroxylated hexagonal boron nitride nanosheets.
[0038] B2. Weigh 50g of the above-mentioned hydroxylated hexagonal boron nitride nanosheets and add them to 750g of 90% ethanol aqueous solution. Disperse the solution by ultrasonication for 30min to form a uniform dispersion. Add 2g of silane coupling agent KH-550, adjust the pH of the system to 5 with glacial acetic acid, heat to 70℃, and stir for 6h to carry out grafting modification. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate 5 times with anhydrous ethanol and dry it under vacuum at 100℃ for 7h to obtain modified hexagonal boron nitride nanosheets.
[0039] Example Example 1 A high-performance polypropylene cable sheath, the raw material composition and dosage of which are shown in Table 1, wherein the molecular weight of polypropylene is 250,000, the molecular weight of ethylene-octene copolymer is 100,000, the polytetrafluoroethylene in-situ supported wollastonite whiskers are selected from the polytetrafluoroethylene in-situ supported wollastonite whiskers prepared in Preparation Example 1, the modified hexagonal boron nitride nanosheets are selected from the modified hexagonal boron nitride nanosheets prepared in Preparation Example 4, the compatibilizer is maleic anhydride grafted polypropylene, the antioxidant is antioxidant 1010, the additive is polyethylene wax and calcium stearate mixed in a mass ratio of 2:1, and the light stabilizer is hindered amine light stabilizer 944.
[0040] A method for preparing a high-performance polypropylene cable sheath includes the following steps: S1. Polypropylene, ethylene-octene copolymer, polytetrafluoroethylene in-situ supported wollastonite whiskers, modified hexagonal boron nitride nanosheets, aluminum hydroxide, carbon black, compatibilizer, antioxidant, light stabilizer and additives are put into a high-speed mixer and mixed at 70℃ and 900r / min for 6min to obtain a premix. S2. The premixed material is added to a twin-screw extruder, melt-blended, extruded, water-cooled, and pelletized to obtain cable sheath granules. The cable sheath granules are added to a single-screw extruder, melt-plasticized, and extruded to coat the surface of the cable core. Then, the material is shaped, drawn, and wound in a cooling water tank to obtain a high-performance polypropylene cable sheath.
[0041] Example 2 A high-performance polypropylene cable sheath, the raw material composition and dosage of which are shown in Table 1, wherein the molecular weight of polypropylene is 350,000, the molecular weight of ethylene-octene copolymer is 150,000, the polytetrafluoroethylene in-situ supported wollastonite whiskers are selected from the polytetrafluoroethylene in-situ supported wollastonite whiskers prepared in Preparation Example 2, the modified hexagonal boron nitride nanosheets are selected from the modified hexagonal boron nitride nanosheets prepared in Preparation Example 5, the compatibilizer is maleic anhydride grafted polypropylene, the antioxidant is antioxidant 1010, the additive is polyethylene wax and calcium stearate mixed at a mass ratio of 2.5:1, and the light stabilizer is hindered amine light stabilizer 944.
[0042] A method for preparing a high-performance polypropylene cable sheath includes the following steps: S1. Polypropylene, ethylene-octene copolymer, polytetrafluoroethylene in-situ supported wollastonite whiskers, modified hexagonal boron nitride nanosheets, aluminum hydroxide, carbon black, compatibilizer, antioxidant, light stabilizer and additives are put into a high-speed mixer and mixed at 78℃ and 1100r / min for 9min to obtain a premix. S2. The premixed material is added to a twin-screw extruder, melt-blended, extruded, water-cooled, and pelletized to obtain cable sheath granules. The cable sheath granules are added to a single-screw extruder, melt-plasticized, and extruded to coat the surface of the cable core. Then, the material is shaped, drawn, and wound in a cooling water tank to obtain a high-performance polypropylene cable sheath.
[0043] Example 3 A high-performance polypropylene cable sheath, the raw material composition and dosage of which are shown in Table 1, wherein the molecular weight of polypropylene is 450,000, the molecular weight of ethylene-octene copolymer is 200,000, the polytetrafluoroethylene in-situ supported wollastonite whiskers are selected from the polytetrafluoroethylene in-situ supported wollastonite whiskers prepared in Preparation Example 3, the modified hexagonal boron nitride nanosheets are selected from the modified hexagonal boron nitride nanosheets prepared in Preparation Example 6, the compatibilizer is maleic anhydride grafted polypropylene, the antioxidant is antioxidant 1010, the additive is polyethylene wax and calcium stearate mixed in a mass ratio of 3:1, and the light stabilizer is hindered amine light stabilizer 944.
[0044] A method for preparing a high-performance polypropylene cable sheath includes the following steps: S1. Polypropylene, ethylene-octene copolymer, polytetrafluoroethylene in-situ supported wollastonite whiskers, modified hexagonal boron nitride nanosheets, aluminum hydroxide, carbon black, compatibilizer, antioxidant, light stabilizer and additives are put into a high-speed mixer and mixed at 85℃ and 1200r / min for 12min to obtain a premix. S2. The premixed material is added to a twin-screw extruder, melt-blended, extruded, water-cooled, and pelletized to obtain cable sheath granules. The cable sheath granules are added to a single-screw extruder, melt-plasticized, and extruded to coat the surface of the cable core. Then, the material is shaped, drawn, and wound in a cooling water tank to obtain a high-performance polypropylene cable sheath.
[0045] Table 1. Raw material composition and dosage (kg) of polypropylene cable sheaths in Examples 1-3
[0046] Example 4 A high-performance polypropylene cable sheath differs from Example 3 in that: in this example, the polytetrafluoroethylene in-situ loaded wollastonite whiskers are selected from the polytetrafluoroethylene in-situ loaded wollastonite whiskers prepared in Example 1; and the modified hexagonal boron nitride nanosheets are selected from the modified hexagonal boron nitride nanosheets prepared in Example 5.
[0047] Example 5 A high-performance polypropylene cable sheath differs from Example 3 in that: in this example, the polytetrafluoroethylene in-situ loaded wollastonite whiskers are selected from the polytetrafluoroethylene in-situ loaded wollastonite whiskers prepared in Example 2; and the modified hexagonal boron nitride nanosheets are selected from the modified hexagonal boron nitride nanosheets prepared in Example 4.
[0048] Example 6 A high-performance polypropylene cable sheath differs from Example 3 in that the additive in this example is calcium stearate.
[0049] Example 7 A high-performance polypropylene cable sheath, which differs from Example 3 in that the antioxidant in this example is antioxidant 168.
[0050] Comparative Example Comparative Example 1 A cable sheath material was prepared according to Example 1 in the patent application document with publication number CN112126156A entitled "A Radiation-Resistant Polypropylene Cable Sheath Material".
[0051] Comparative Example 2 A high-performance polypropylene cable sheath differs from Example 3 in that: in this comparative example, polytetrafluoroethylene-loaded wollastonite whiskers and modified hexagonal boron nitride nanosheets were not added, and the difference was made up with polypropylene.
[0052] Comparative Example 3 A high-performance polypropylene cable sheath differs from Example 3 in that: in this comparative example, an equal amount of wollastonite whiskers is used instead of polytetrafluoroethylene-loaded wollastonite whiskers.
[0053] Comparative Example 4 A high-performance polypropylene cable sheath differs from Example 3 in that an equal amount of hexagonal boron nitride nanosheets are used instead of modified hexagonal boron nitride nanosheets in this comparative example.
[0054] Performance testing The cable sheath materials prepared in each embodiment and comparative example were made into standard test samples, cooled, cut into samples of corresponding specifications, and subjected to performance testing after standing for 24 hours.
[0055] (1) Abrasion resistance: The test was conducted in accordance with GB / T 1689-2014 "Determination of abrasion resistance of vulcanized rubber (Akron abrasion tester method)". The sample size was φ16mm×8mm, the grinding wheel grit size was 40 mesh, the test load was 26.7N, the total sliding distance was 1.61km, the abrasion volume of the sample was tested and calculated, and the smaller the value, the better the abrasion resistance.
[0056] (2) Shore D hardness: The test was conducted in accordance with GB / T 2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester". A type D Shore hardness tester was used. Five different positions were tested for each sample, and the arithmetic mean was taken to characterize the surface scratch resistance and deformation resistance of the material.
[0057] (3) Notched impact strength of simply supported beam: The test was conducted in accordance with GB / T 1043.1-2008 "Determination of impact performance of simply supported beams of plastics - Part 1: Non-instrumental impact test". The sample size was 80mm×10mm×4mm, with a type A notch. The test environment temperature was 23℃ to characterize the low-temperature toughness and impact resistance of the material.
[0058] (4) Tensile properties: The tensile properties of plastics were tested in accordance with GB / T 1040.2-2006 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". 1BA type specimens were used, and the tensile rate was 50 mm / min. The tensile strength and elongation at break were tested to characterize the basic mechanical properties of the material.
[0059] Table 2 Test Results
[0060] Overall, the wear resistance of each embodiment of this application is significantly improved compared to the prior art. Compared with Comparative Example 1, which represents the prior art solution, the Akron wear volume reduction of the embodiments of this application exceeds 70%, solving the core defect of poor wear resistance of polypropylene cable sheaths. This application, through structural modification of the core filler and synergistic design of the system, fundamentally weakens the impact of the above two types of adverse factors, while the basic mechanical properties of the material, such as impact toughness and tensile strength, remain within the applicable range for cable sheaths, meeting the requirements for normal laying and service.
[0061] Comparing the test results of Comparative Example 2 and Example 3, it can be seen that the in-situ supported wollastonite whiskers and modified hexagonal boron nitride nanosheets on polytetrafluoroethylene (PTFE) are the core functional sources of improved wear resistance. Comparative Example 2, without the addition of the two modified fillers, showed a wear volume approximately three times that of Example 3, indicating a significant difference in wear resistance. The underlying logic is that the hybrid reinforcement system composed of one-dimensional wollastonite whiskers and two-dimensional hexagonal boron nitride nanosheets can build a rigid load-bearing network in the matrix, effectively improving the surface hardness and resistance to compressive deformation, and reducing the ploughing depth and material spalling during friction. Simultaneously, the PTFE anchored on the whisker surface and the lamellar slip characteristics of boron nitride create a dual lubrication effect, forming a continuous low-resistance transfer film at the friction interface, reducing the interfacial friction coefficient, and achieving a significant improvement in wear resistance.
[0062] Further comparison of Comparative Examples 3 and 4 with Example 3 visually demonstrates the technical value of the two filler modification designs. Comparative Example 3, which uses ordinary wollastonite whiskers to replace the in-situ loaded whiskers, only provides a single rigidity enhancement effect, lacking a continuous and stable interfacial lubrication effect. Furthermore, the insufficiently activated whiskers have limited interfacial bonding with the matrix, resulting in micro-filler detachment during friction. Consequently, the wear volume is nearly double that of Example 3. Comparative Example 4, which uses unmodified hexagonal boron nitride to replace the modified nanosheets, suffers from poor compatibility between the sheets and the polyolefin matrix, leading to easy stacking and agglomeration and easy peeling from the matrix. This not only fails to provide uniform interlayer lubrication but also creates internal stress concentration points, accelerating material wear. Its wear performance is also significantly worse than Example 3. These results confirm that the in-situ loaded lubrication layer and surface organic modification design effectively solve the common problems of easy filler detachment and easy lubricant migration and precipitation, representing the key innovation in improving wear resistance.
[0063] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-performance polypropylene cable sheath, characterized in that, Including the following parts by weight of raw materials: 60-80 parts of polypropylene; 8-18 parts of ethylene-octene copolymer; 6-15 parts of polytetrafluoroethylene in situ supported on wollastonite whiskers; 3-10 parts of modified hexagonal boron nitride nanosheets; 10-20 parts aluminum hydroxide; 1-3 parts carbon black; 2-5 parts compatibilizer; Antioxidant 0.3-1.2 parts; Light stabilizer 0.2-0.8 parts; Additives: 0.5-1.5 parts; The polytetrafluoroethylene in-situ supported wollastonite whiskers are obtained by in-situ deposition of nano-polytetrafluoroethylene particles on the surface of wollastonite whiskers as a substrate. The modified hexagonal boron nitride nanosheets are prepared by hydroxylating and etching hexagonal boron nitride nanosheets and then grafting silane coupling agents onto them.
2. The high-performance polypropylene cable sheath according to claim 1, characterized in that, The polytetrafluoroethylene-supported wollastonite whiskers were prepared by the following method: A1. Add wollastonite whiskers to an aqueous sodium hydroxide solution, heat to 70-90℃, stir for 2-4 hours, filter and wash, and dry at 100-110℃ for 6-8 hours to obtain hydroxylated wollastonite whiskers. A2. Add hydroxylated wollastonite whiskers to deionized water and ultrasonically disperse for 15-30 min. Then add polytetrafluoroethylene dispersion emulsion, adjust the pH of the system to 3-4, heat to 65-75℃, and stir for 3-5 h. Then filter the suspension, wash the filter cake with deionized water 3-5 times, dry at 100-120℃ for 4-6 h, and then place it in a muffle furnace and sinter at 360-380℃ under a nitrogen atmosphere for 1-2 h. After cooling, pulverize to obtain polytetrafluoroethylene-supported wollastonite whiskers.
3. The high-performance polypropylene cable sheath according to claim 2, characterized in that: In step A1, the mass concentration of the sodium hydroxide aqueous solution is 5%-10%; the mass ratio of the wollastonite whiskers to the sodium hydroxide aqueous solution is 1:(8-12).
4. The high-performance polypropylene cable sheath according to claim 2, characterized in that: In step A2, the mass ratio of the hydroxylated wollastonite whiskers, deionized water, and polytetrafluoroethylene dispersion emulsion is 1:(9-12):(0.3-0.8); the solid content of the polytetrafluoroethylene dispersion emulsion is 20%-30%.
5. The high-performance polypropylene cable sheath according to claim 1, characterized in that, The modified hexagonal boron nitride nanosheets were prepared using the following method: B1. Add hexagonal boron nitride nanosheets to a mixed acid solution, ultrasonically disperse for 20-40 min, heat to 85-95℃, reflux etching for 5-7 h, and obtain hydroxylated hexagonal boron nitride nanosheets after filtration, washing and drying. B2. Add hydroxylated hexagonal boron nitride nanosheets to an ethanol solution and ultrasonically disperse for 20-30 min. Then add silane coupling agent KH-550, adjust the pH of the system to 4-5 with glacial acetic acid, heat to 60-70℃, and stir for 4-6 h. After the reaction is complete, centrifuge, wash with ethanol 3-5 times, and vacuum dry at 80-100℃ for 5-7 h to obtain modified hexagonal boron nitride nanosheets.
6. The high-performance polypropylene cable sheath according to claim 5, characterized in that: In step B1, the mixed acid solution is concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (3-4):1; the mass ratio of the hexagonal boron nitride nanosheets to the mixed acid solution is 1:(20-30).
7. The high-performance polypropylene cable sheath according to claim 5, characterized in that: In step B2, the mass concentration of the ethanol solution is 80%-90%, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the ethanol solution is 1:(10-15), and the amount of silane coupling agent KH-550 added is 1%-4% of the mass of the hydroxylated hexagonal boron nitride nanosheets.
8. The high-performance polypropylene cable sheath according to claim 1, characterized in that: The molecular weight of the polypropylene is 250,000 to 450,000.
9. A high-performance polypropylene cable sheath according to claim 1, characterized in that: The additive is a mixture of polyethylene wax and calcium stearate in a mass ratio of (2-3):1; the compatibilizer is maleic anhydride-grafted polypropylene.
10. A method for preparing a high-performance polypropylene cable sheath according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Polypropylene, ethylene-octene copolymer, polytetrafluoroethylene in-situ supported wollastonite whiskers, modified hexagonal boron nitride nanosheets, aluminum hydroxide, carbon black, compatibilizer, antioxidant, light stabilizer and additives are put into a high-speed mixer and mixed at 70-85℃ and 900-1200r / min for 6-12min to obtain a premix. S2. The premixed material is added to a twin-screw extruder, melt-blended, extruded, water-cooled, and pelletized to obtain cable sheath granules. The cable sheath granules are added to a single-screw extruder, melt-plasticized, and extruded to coat the surface of the cable core. Then, the material is shaped, drawn, and wound in a cooling water tank to obtain a high-performance polypropylene cable sheath.
Citation Information
Patent Citations
Irradiation-resistant polypropylene cable sheath material
CN112126156A